Chemical composition, antimicrobial and antioxidant activity of leaves essential oil the Myrcia palustris DC. (MYRTACEAE) (Research, Society and Development, 2021)
Brazil has the greatest biodiversity in the world and in this context, its native species become an alternative in the search for bioactive molecules for bioprospecting antimicrobials and natural antioxidants. Belonging to the Myrtaceae family, the species Myrcia palustris DC, popularly known as pintagueira-do-mato, does not present studies regarding its biological activities and chemical composition. Therefore, the objective of this work was to determine the chemical composition of the essential oil of M. palustris by gas chromatography coupled with mass spectrometry (GC-MS), to evaluate its antimicrobial activity by the broth microdilution technique and the antioxidant activity by the broth technique. 2,2-diphenyl-1-picryl-hydrazyl (DPPH). The total yield from the essential oil hydrodistillation technique was 0.35%. The GC-MS revealed the presence of 28 compounds, the majority being from the sesquiterpenes class. Antimicrobial activity was observed for all Gram-positive bacteria (Bacillus subtilis, Enterococcus faecalis, Staphylococcus aureus) with the exception of Staphyloccocus epidermidis. Regarding Gram-negatives, there was an inhibitory activity only for Shigella flexneri. For yeast Candida albicans, no inhibitory or fungicidal activity was observed. The essential oil showed a capacity to reduce DPPH radicals up to 82.81%, confirming its antioxidant potential. It is suggested that the antimicrobial and antioxidant action present in the essential oil of M. palustris is related to the presence of the major compounds α-Guaieno (25.89%), α-Bulnesene (13.39%) and β-Selinene (4, 76%).